Transtorno do espectro autista: um olhar acerca das práticas docentes nas aulas de educação física em Tocantinópolis. - Pimentel, Kamilah Borges (Universidade Federal do Tocantins, 2021)
Autistic Spectrum Disorder (ASD) is a neurodevelopmental disorder where communication difficulties, social interaction, repetitive and stereotyped behavior patterns occur together with restricted interests. Studies show that teachers who work with physical education at school feel limited and insecure in including students with and without disabilities in the same class. The present work aimed to identify the teaching practices and difficulties in physical education classes that present students diagnosed with ASD in the public school system in the city of Tocantinópolis-TO. In methodological terms, this research is characterized as observational, transversal, descriptive and with a qualitative and quantitative approach, using a form with open and closed questions applied through structured interviews with teachers from municipal and state schools. The results showed that a large part of the teachers did not have adequate preparation or training to work with the said audience of students, although not all had difficulties, and those who did not use any methodology to include them because they do not know how to intervene. It is concluded that most of the teachers emphasized the importance of the family group and caregivers of the students for their inclusion in the classes and that the flaws in the training and qualification are present during and after the graduation independent of the course, making the teaching practice difficult in what it says respect to Physical Education classes that teachers must include students with ASD.